Rancangan dan Implementasi Aplikasi Kepramukaan “Strong Scout” Berbasis Android - Wicaksono, Ridho Satrianie; Putra, Berlian Juliartha Martin; Hikmahwan, Bagus (Journal of Electrical, Electronic, Mechanical, Informatic and Social Applied Science, 2022)
Scouting is one of the extracurricular activities that exist from elementary school, junior high school, high school, vocational high school, to college level. Scouts themselves are extras who have an active role in educating character, having a nationalist, leader, social and community spirit. There is some scouting material that is quite a lot for scout members to learn. Therefore, the Android-based “Strong Scout” scouting application is expected to increase interest and members of the scout extracurricular activities themselves in learning. This application is designed using the waterfall method. System design using erd, dfd and activity diagrams. The system uses a sqlite DBMS and is based on Android. This research resulted in an application that can be run according to the menu and its function, starting from the material, practice questions and the process. This android-based scouting application can make it easier for members in scouting activities and can increase the interest of students to take scout extracurricular activities.